Advanced materials based on new structurally designed poly(naphthylimide‐amide)s1. Issue 3 (11th September 2014) - Constantin, Catalin‐Paul; Damaceanu, Mariana‐Dana; Bruma, Maria; Pinteala, Mariana
<x xml:space="preserve">Abstract</x> Novel thermostable poly(naphthylimide‐amide)s were synthesized. They form nanometric aggregates in solutions and thin films having self‐assembled micellar structures. These polymers emit blue or white light and have electron‐transporting ability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>